2015
DOI: 10.1681/asn.2015050580
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Factor H R1210C Association with Ocular and Renal Diseases

Abstract: The complement factor H (FH) mutation R1210C, which was described in association with atypical hemolytic uremic syndrome (aHUS), also confers high risk of agerelated macular degeneration (AMD) and associates with C3 glomerulopathy (C3G). To reveal the molecular basis of these associations and to provide insight into what determines the disease phenotype in FH-R1210C carriers, we identified FH-R1210C carriers in our aHUS, C3G, and AMD cohorts. Disease status, determined in patients and relatives, revealed an ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…The R1210C mutant is highly penetrant and also leads to an earlier age of onset compared to the overall AMD population (mean age of onset 65 versus 71 years). This association of the R1210C mutant with AMD has now been shown by several groups (see below) and has been reported in aHUS patients (55, 56) as well as in C3G (40, 57). …”
Section: Factor H Mutationssupporting
confidence: 72%
See 2 more Smart Citations
“…The R1210C mutant is highly penetrant and also leads to an earlier age of onset compared to the overall AMD population (mean age of onset 65 versus 71 years). This association of the R1210C mutant with AMD has now been shown by several groups (see below) and has been reported in aHUS patients (55, 56) as well as in C3G (40, 57). …”
Section: Factor H Mutationssupporting
confidence: 72%
“…Mutations in FH have been described in AMD, aHUS, and C3G. Of interest and unexplained, although the same mutation may be found in more than one disease, more commonly, they appear to be preferentially restricted to one disease (40). …”
Section: Factor H Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the D1119G mutant still efficiently competes with wild type FH19 -20 for C3b/C3d, the mutation might affect the self-association characteristics of the two C-terminal CCPs, preventing binding to C3b/C3d. Recently, the aHUS/AMD-associated R1210C mutation has been shown to introduce a gain of function defect, as it enables the protein to form covalent bonds with serum albumin (49,50). The R1210A mutant used in the current study lacks the surface-exposed cysteine; therefore, the observed effects can likely be attributed to a decrease in electrostatic interactions with FH19 -20 ligands.…”
Section: Discussionmentioning
confidence: 93%
“…Through the introduction of a cysteine residue, Arg1210Cys forms covalent interactions with human serum albumin (Sanchez-Corral et al, 2002). It has been postulated that it is the albumin bound to FH rather than any functional defect of the protein itself that eventually disrupts FH function (Recalde et al, 2016). …”
Section: Functional Implication Of Rare Genetic Variantsmentioning
confidence: 99%